Fireplace and woodstove fine particle emissions from combustion of western Mediterranean wood types - Alves, Célia (2011)
Wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europea and Quercus ilex rotundifolia), and briquettes produced from forest biomass waste were burned in a fireplace and in a woodstove to determine the chemical composition of fine particle (PM2.5) emissions. Samples were analysed for organic and elemental carbon (OC/EC), water soluble ions (Na+, NH4 +, K+, Mg2+, Ca2+, Cl−, NO3 − and SO4 2−) and 67 elements. The PM2.5 emission factors (g kg−1 fuel burned, dry basis) were in the ranges 9.9–20.2 and 4.2–16.3, respectively, for the fireplace and the woodstove. Organic carbon contributed to about 50% of the fine particle mass in the emissions from every wood species studied in both burning appliances. The carbonaceous component of PM2.5 was dominated by organic carbon, accounting for more than 85% of the total carbon (TC): OC/TC ranged from 0.85 to 0.96 (avg. 0.92) for the fireplace and from 0.86 to 0.97 (avg. 0.93) for the woodstove. The water-soluble ions accounted for 0.64 to 11.3% of the PM2.5 mass emitted from the fireplace, whereas mass fractions between 0.53 and 13.6% were obtained for the woodstove. The golden wattle wood smoke showed a much higher ionic content than the emissions from the other wood types. Trace elements represented 0.4 to 2.5% and 0.2 to 2.2% of the PM2.5 mass emitted, respectively, from the fireplace and the woodstove, which corresponded to average total emissions of 132±77.3 mg kg−1 and 93.4± 60.8 mg kg−1 of wood burned. Among these, K, Pb, Al, Mn and Sr were present in all samples. From the emission profiles of the individual experiments, composite wood combustion profiles are suggested with the aid of a cluster analysis.